DESTRUCTION OF THE INTERSTELLAR CLOUDS BY THESHOCK WAVES - Matvienko, E. E.; Shchekinov, Yu. A. (Одеські астрономічні публікації, 2008)
We study the influence of the interstellar cloud structure irregularity on the dynamics of its destruction by a supernova shock wave. It is shown that irregular clouds are destroyed twice quickly as the spherical ones. Subject to that the fragments of the clouds sustain high-density and do not mix with the intercloud gas.